The role of LKB1 in prostate cancer: implications for tumor progression and therapy - Liang, Yuwei; Cao, Hongliang; Tang, Zhijun; Li, Shuxin; Yang, Gang; Dong, Shuai; Du, Hao; Wang, Jinguo (Frontiers in Cell and Developmental Biology, 2025)
Liver kinase B1 (LKB1/STK11) is a key tumor suppressor that regulates cellular metabolism, epigenetic states, and multiple signaling pathways in prostate cancer (PCa). Recent studies reveal that both genetic and non-genetic LKB1 loss drives metabolic reprogramming, lineage plasticity, and treatment resistance, mainly through dysregulation of the AMP-activated protein kinase (AMPK)/mechanistic target of rapamycin (mTOR), signal transducer and activator of transcription 3 (STAT3), and Hedgehog (Hh) pathways. This review summarizes current evidence on LKB1-centered networks in PCa, highlighting the potential link between LKB1 inactivation, epigenetic remodeling, and aggressive tumor phenotypes. Special attention is given to recent studies on the impact of combined LKB1 and Phosphatase and Tensin Homolog (PTEN) loss on tumor differentiation. Finally, we discuss emerging therapeutic strategies aimed at the metabolic and epigenetic features of LKB1-deficient PCa, with a focus on the prospects for biomarker-driven precision medicine to address resistance and improve patient outcomes.